Energy efficient modulation technique on 10Gb/s coherent detection optical OFDM - Rahman, M. Tawfiq; Faruqi, S. I.; Islam, Md. Rafiqul; Abdullah, Khaizuran (2015)
The performance of energy efficiency in a radio-over-fiber system utilizing M-QAM (quadrature amplitude modulation), OOK (On-Off-keying) and M-PAM (Pulse amplitude modulation) is highlighted. The performance of single channel CO-OFDM and with 10GHz channels pacing at 10-Gb/s data rate is shown through the optisystem for different modulation schemes and different fiber lengths at different receiving power levels. The experimented results have been achieved over 100km, 400km, 600km and 1000 km distances to study the effect of power consumption at the receiver end with different modulation schemes. In short distance PAM performs quite well and 16 QAM has worst results. In long distance OOK obtain the highest receive power and high order QAM receive the lowest power for the same distance. In middle range 600km, OOK is better and 128QAM has high loss 16QAM & PAM was almost same performance. To increase BER performance of M-QAM, amplifier power should increase trade off but noise level and signal quality also has to maintain. Furthermore, the simulation results expose that the transmission length increased and also the receive power level decreased for fiber attenuation, dispersion and low power of the laser. The results show the relationship of transmission distance and receive power level, and between bit error rate and optical signal to noise ratio (OSNR).